3D-Printed Facet Optics: Novel Adjustable Technical Optics Inspired by Compound Eyes - Drack, Manfred; Berger, Alexander; Ettinger, Bernhard; Gebeshuber, Ille C. (Frontiers in Materials, 2020)
Bio-inspired by compound eyes in insects, the authors identify advantages of such an optical system and propose a novel optics that combines basic principles from compound eyes with an additional technical zooming feature. The 3D-printed, bio-inspired fiber optic set-up is based on ommatidia, the small single components of compound eyes. The advantageous aspects that are transferred from the inspiring organisms are that no focusing on objects is needed and a maximum depth of focus is always achieved. Two adjustable technical features are an adjustable field of view per pixel and a zooming possibility, not found in animals. Prototypes were produced as a proof of concept. One of them was manufactured using a stereolithography 3D printer. They were positively tested with regard to the implemented features. Optional further functionalities and developments are discussed. Possible applications of the 3D-printed, bio-inspired designs are optical devices that benefit from adjusting the field of view per pixel to zooming. Suggested are novel microscopes and screens with built-in cameras enabling online eye-to-eye communication without having to concentrate on the location of a camera.